If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y + 2x) + -4x = 0 Reorder the terms: (2x + 3y) + -4x = 0 Remove parenthesis around (2x + 3y) 2x + 3y + -4x = 0 Reorder the terms: 2x + -4x + 3y = 0 Combine like terms: 2x + -4x = -2x -2x + 3y = 0 Solving -2x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -2x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 -2x + 0 = 0 + -3y -2x = 0 + -3y Remove the zero: -2x = -3y Divide each side by '-2'. x = 1.5y Simplifying x = 1.5y
| 3(7+2(3)-3)= | | -100=-7x-x-4 | | -(6k-1)=-4-7k | | -2/5=-1/2u-5/3 | | 500=(26.25)(x)(18) | | (y-3)(4y+7)=0 | | ln3/.5 | | 4x+1-x=-20 | | 47=-2x+7x+7 | | 2x+(3y-4x)= | | 4x+1-x=-2 | | x+(0.18x)=7184 | | -5(15+6y)+5y=0 | | .2w+.2w=-1.2w+.33 | | x+(0.18x)=7183 | | 2/5*x=3==13 | | 42/36=35/30 | | -16=-x+5x-4 | | 8/3=40/15 | | 7y+y(3-4)= | | 3y-3-4y=2 | | 32/18=48/27 | | X/x-13=3 | | 6g^3+7h+-8g^3= | | 7/12=14/24 | | .25v-.43=.29v-.25 | | 4.650/5 | | 6/21=8/28 | | 2x-5-x=x+3 | | 17=3w-10 | | -9(u+1)=-6u-27 | | 1/4a-7=25 |